STRUKTUR KETENAGAKERJAAN DAN PARTISIPASI ANGKATAN KERJA DI PEDESAAN INDONESIA: ANALISIS HASIL SAKERNAS 2006 - Setiawan, Nugraha (Lampung University)
The study is aimed at analyzing labor structure in rural area, by carrying out study on working age population, labor force, and labor force participation rate. Secondary data analysis approach was used in this study. The data form Sakernas (National Labor Force Survey) 2006 was analyzed by a descriptive statistical analysis. The result of the study showed that proportion of working age population and labor force in rural area it was more younger and lower education than urban area. However, if we take look at rural labor force participation rate was higher than the urban area, in all ages and education attainment groups. It may raise concern that labor force in the rural areas are greater than the possible field work available.